Effect of erythromycin‐doped calcium polyphosphate scaffold composite in a mouse pouch infection model. Issue 6 (18th December 2013) - Ren, Weiping P.; Song, Wei; Esquivel, Amanda O.; Jackson, Nancy M.; Nelson, Matthew; Flynn, Jeffery C.; Markel, David C.
Abstract We previously showed that strontium‐doped calcium polyphosphate (SCPP) scaffold with poly(vinyl alcohol) (PVA) coating extended the impregnated erythromycin (EM) release. In this study, we examined the bactericidal effect of EM‐doped SCPP (SCPPEM) scaffolds with PVA coating in a Staphylococcus aureus (S. aureus) infected mouse pouch. SCPP scaffolds with or without 5% EM, and SCPPEM scaffolds coated with PVA (with or without 5% EM) were prepared. Scaffolds were implanted in the pouch of BALB/c mice, followed by inoculation of 1 × 103 colony‐forming units of S. aureus. Mice were sacrificed 14 days after surgery. Pouch tissues and scaffolds were collected for histology, scanning electron microscopy, and microbiological analysis. In the absence of SCPP scaffolds, the pouch infection was eliminated by the host immune surveillance. In the presence of SCPP scaffolds, both the pouch tissues and scaffolds were infected, but SCPPEM scaffolds successfully inhibited bacterial growth. Although PVA coating of SCPPEM scaffolds enhanced bacterial growth, incorporation of EM into PVA coating inhibited growth. In conclusion, BALB/c mice were capable of eradicating a low grade S. aureus infection. SCPP protected S. aureus growth from host immune surveillance. Though PVA coating sustained EM release in vitro, it was unable to inhibit bacterial growth because PVA gel matrix provided a temporary shelter for bacteria to grow and slowed the EM release from SCPP scaffold. To guarantee a sufficient inhibition of bacterial growth at the initial stage, embedding EM or other antibiotics in the PVA coating is also essential. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1140–1147, 2014.